Effects of a stepwise handovers ISBARQ programme among nursing college students - Yoon Goo Noh; Insook Lee (Wiley, 2020)
Abstract Background Due to a lack of standardized guidelines, it is necessary to verify the effectiveness of educational programmes for nursing students' systematic handover training. Aims This study aimed to develop a stepwise nursing handover programme and to examine its effects on awareness of handover Situation, Background, Assessment, Recommendation, communication self‐efficacy and satisfaction with handover education. Design This was a single‐group repeated measures ANOVA study. Methods This study was conducted in a nursing department, using a convenience sample of 25 senior nursing students from April 2 to June 22, 2018. The programme was divided into lectures, scenario role‐playing and nursing case role‐playing. The research questions were analysed using repeated measures ANOVA. Results Awareness of handover Situation, Background, Assessment, Recommendation, communication self‐efficacy and satisfaction with handover education gradually increased after each step of the programme. The stepwise nursing handover programme, progressing from low to high levels of learning, can be used to improve the nursing handover system and handover communication ability.